ANALISIS GAYA BAHASA PADA ACARA STAND UP COMEDY DI KANAL YOUTUBE STAND UP KOMPAS TV - Siti Mariyam; Herlina Sugiarti, Dewi; Dinar Pratiwi, Wienike (UNIVERSITAS PGRI YOGYAKARTA, 2025)
ABSTRACT This study aims to analyze the laungae style in Stand Up Comedy shows on the Youtube channel Stand Up Kompas TV. The focus of this study is to analyze language style based on word choice, language style based on sentence structure, and language style based on indirect meaning (figurative language style). This study uses a qualitative methode with a descriptive approach. The subjects of this atudy were selected standup comedy videos uploaded on the Youtube channel Stand Up Kompas TV, while the object of the study was the language style used in the selected videos, with the researcher as the instrument. The data collection techniques used were documentation and transcription. The analysis technique in this sudy follows the opinion of Miles and Huberman (in Hardani, et al., 2020:163), which includes data reduction, data presentation, and drawing conclusions. The results of this study found 8 data from the typeof language style based on word choice; 135 data from the type of language style based on sentence structure; and 126 data from the type of language style based on indirect meaning. These types of language style totaled 269 data. Keywords: Languade Style, Stand Up, and Stand Up Kompas Tv Youtube Channel.